Mn-doped 0.15Pb(Yb1/2Nb1/2)O3-0.48Pb(Mg1/3Nb2/3)O3-0.37PbTiO3 piezoelectric ceramics for high performance high-power transducers - Lee, Dong-Gyu; Go, Su-hwan; Yoo, Il-Ryeol; Choi, Seong-Hui; Kim, Yi Yeon; Kim, Hyun Soo; Hur, Sunghoon; Kang, Heemin; Baik, Jeong Min; Park, Yong Seok; Nahm, Sahn; Kang, Chong-Yun; et al. (Pergamon Press Ltd., 2023)
For high-power transducer applications, the piezoelectric materials should fulfill specific requirements of a high mechanical quality factor (Q(m)), a high piezoelectric strain coefficient (d(ij)), and a high Curie phase transition temperature (T-c). In this study, we present an investigation of the structural, piezoelectric, and high-power characteristics of Mn-doped 0.15Pb(Yb1/2Nb1/2)O-3-0.48Pb(Mg1/3Nb2/3)O-3-0.37PbTiO(3) (0.15PYN-0.48PMN-0.37PT) ceramics. The introduction of Mn dopants led to an increase in the tetragonal phase fraction within the 0.15PYN-0.48PMN-0.37 PT ceramics and the formation of oxygen vacancies, consequently significantly enhancing Q(m) due to their synergistic effect. Despite the hardening effect, the high value of the piezoelectric coefficient (d(33)) was maintained due to the increase in grain size. Particularly, the specimen doped with 3 mol% of Mn exhibited excellent piezoelectric properties of d(33) = 345 pC/N, Q(m) = 1159, and T-c = 207 degrees C. This specimen displayed a high vibration velocity of 0.6 m/s under the condition of equilibrium Delta T < 20 degrees C (temperature rise from initial temperature), thereby confirming its immense potential for high-power transducer applications.